Transforming Buwuhan Tradition In Accounting Perspective: Exploring Value And Economic Impact - Sulistyowati, Rina; Arfamaini, Revi; Rahmawaty; Meilia, Frizkana (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The research aims to transform the Buwuhan tradition through an accounting perspective by exploring its value and economic impact. It will analyze the financial implications, assess value creation, and investigate the application of modern accounting practices to enhance economic activities related to Buwuhan. The study will also propose strategies for sustaining and expanding the tradition, aiming to balance cultural preservation with economic growth. Design/methodology/approach: This research uses literature research methods (library research). Research This literature research which states that literature research is known for activities related to collecting library data, reading, and recording and processing research materials. Literature research limits its activities to only materials derived from libraries without the need for field research. Research Findings: it is explained that the meaning in wages and hapolas is almsgiving, love, and sincere and sincere intentions. The absence of financial recording and reporting shows that this practice has a different concept of accountability from generally accepted accounting, namely accountability based on love.Theoretical Contribution/Originality: his research applies modern accounting to the Buwuhan tradition, bridging cultural heritage and economic analysis. It offers a framework for quantifying and enhancing the financial and social value of cultural practices, providing new insights for accounting and aiding community leaders in balancing cultural preservation with economic development